Implications of Isolated Para-Aortic Lymph Node Metastasis in Endometrial Cancer: A Large-Scale, Multicenter, and Retrospective Study - Li, Wenting; Jiang, Jie; Fu, Yu; Shen, Yuanming; Zhang, Chuyao; Yao, Shuzhong; Xu, Congjian; Xia, Min; Lou, Ge; Liu, Jihong; Lin, Bei; Wang, Jianliu; et al. (Frontiers in Medicine, 2021)
Objectives. To systematically evaluate lymph nodes metastatic (LNM) patterns in endometrial cancer (EC) patients underwent complete surgical staging including systematic pelvic and para-aortic lymphadenectomy. Methods. Four thousand and one patients who underwent complete surgical staging including systematic pelvic and para-aortic lymphadenectomy for EC were enrolled from 30 centers in China from 2001 to 2019. We systematically displayed the clinical and prognostic characteristics of patients with various LNMs patterns, especially the PLN-PAN+ (para-aortic lymph node (PAN) metastasis without pelvic lymph node (PLN) metastasis). The efficacy of PAN+ (para-aortic lymph node metastasis) prediction with clinical and pathological features were evaluated.nsnjooaq Results. Overall, 431 of 4,001 patients (10.8%) showed definite LNM according to pathological diagnosis. The PAN+ showed the highest frequency (6.6%) among all metastatic sites. 114 cases (26.5%) were PLN-PAN+(PAN metastasis without PLN metastasis),167 cases (38.7%) showed PLN+PAN-(PLN metastasis without PAN metastasis), and 150 cases (34.8%) metastasized to both regions (PLN+PAN+). There was also 1.9% (51/2,660) of low-risk patients who occurred PLN-PAN+. There are no statistical differences in relapse-free survival (RFS) and disease-specific survival (DSS) among PLN+PAN-, PLN-PAN+, and PLN+PAN+. The sensitivity of gross PLNs, gross PANs, and Lymphovascular space involvement (LVSI) to predict PAN+ were 53.8% (95% CI 47.6-59.9), 74.2% (65.6-81.4), and 45.8% (95% CI 38.7-53.2), respectively. Conclusion. Over one-fourth of EC patients with LMN metastases were PLN-PAN+. PLN-PAN+ shares approximate survival outcomes (RFS and DSS) with other LMN patterns. No effective clinical methods was achieved for predicting PAN+. Thus, PLN-PAN+ is a nonnegligible LMN metastatic pattern that cannot be underestimated in EC, even in low-risk patients.